Implementing prenatal diagnosis based on cell-free fetal DNA: accurate identification of factors affecting fetal DNA yield. - Angela N Barrett; Bernhard G Zimmermann; Darrell Wang; Andrew Holloway; Lyn S Chitty (PLoS ONE)
Objective Cell-free fetal DNA is a source of fetal genetic material that can be used for non-invasive prenatal diagnosis. Usually constituting less than 10% of the total cell free DNA in maternal plasma, the majority is maternal in origin. Optimizing conditions for maximizing yield of cell-free fetal DNA will be crucial for effective implementation of testing. We explore factors influencing yield of fetal DNA from maternal blood samples, including assessment of collection tubes containing cell-stabilizing agents, storage temperature, interval to sample processing and DNA extraction method used. Methods Microfluidic digital PCR was performed to precisely quantify male (fetal) DNA, total DNA and long DNA fragments (indicative of maternal cellular DNA). Real-time qPCR was used to assay for the presence of male SRY signal in samples. Results Total cell-free DNA quantity increased significantly with time in samples stored in K(3)EDTA tubes, but only minimally in cell stabilizing tubes. This increase was solely due to the presence of additional long fragment DNA, with no change in quantity of fetal or short DNA, resulting in a significant decrease in proportion of cell-free fetal DNA over time. Storage at 4 °C did not prevent these changes. Conclusion When samples can be processed within eight hours of blood draw, K(3)EDTA tubes can be used. Prolonged transfer times in K(3)EDTA tubes should be avoided as the proportion of fetal DNA present decreases significantly; in these situations the use of cell stabilising tubes is preferable. The DNA extraction kit used may influence success rate of diagnostic tests.